Catalyzing benzoxazine polymerization with borohydrides to reduce the cure temperature and coloring. (5th December 2022) - Deliballi, Zeynep; Kiskan, Baris; Yagci, Yusuf
Graphical abstract: Highlights: Sodium cyanoborohydride and sodium borohydride are used as catalysts for curing benzoxazines at lower temperatures. These catalysts also alleviated the colorization of polybenzoxazines during the curing process. The catalysts showed constructive effect on the degradation temperatures polybenzoxazines. Abstract: Sodium cyanoborohydride (NaCNBH3 ) and sodium borohydride (NaBH4 ) were used as catalysts to lower the ring-opening polymerization (ROP) temperature of 1, 3-benzoxazines. According to the dynamic scanning calorimeter (DSC) and Fourier transform infrared (FTIR) studies, the onset ROP temperatures of model benzoxazine were decreased by ca. 80 °C. The activation energies of catalyzed ROP were estimated by Kissinger and Ozawa methods. Moreover, the room temperature behavior of the catalysts in benzoxazine was revealed by 1 H NMR and FTIR, and it was found to be dormant at low temperatures and active after 170 °C. Besides catalytic activity, the borohydrides reduced the intense colorization of benzoxazines during curing, and the color changes of catalyzed and uncatalyzed polybenzoxazine samples were measured by colorimetry. Moreover, the thermal stabilities of the catalyzed polybenzoxazines were analyzed and compared to their un-catalyzed counterparts by thermal gravimetric analyses (TGA).